Design of a Detector System in Electrical Installations at Dize Photography Studio - Riski, Alwi; Muhammad Erpandi Dalimunthe; Zuraidah Tharo (INFOKUM, 2025)
The stability of a three-phase power supply is crucial for ensuring the reliable operation of photography studio equipment, which is generally sensitive to electrical disturbances. One common disturbance is phase failure, which can cause equipment damage, reduced work quality, and safety risks. This study aims to analyze and implement a microcontroller-based phase failure detector system capable of detecting abnormal conditions in a photography studio's electrical system quickly and accurately. The system is designed using an ATmega328P microcontroller integrated with voltage sensors on each phase. When one of the phases fails, the system will provide a warning via a buzzer and LED indicator, and can optionally disconnect the load to prevent further damage. Test results show that this detector is capable of detecting the loss of a phase in less than 1 second with an accuracy level of XX% (adjusted based on the results). Thus, this system can improve protection for studio equipment and support more reliable operations.